HUBUNGAN TINGKAT PENGETAHUAN TENTANG COVID-19 TERHADAP KEPATUHAN PELAKSANAAN PHYSICAL DISTANCING PADA MAHASISWA TINGKAT 4 FAKULTAS KEDOKTERAN UNIVERSITAS PEMBANGUNAN NASIONAL VETERAN JAKARTA TAHUN 2020 - Indah Permatasari (2020)
Coronavirus Disease 2019 (COVID-19) is a contagious disease caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). Indonesia has a fairly high prevalence of COVID-19. One of the factors that determines this condition is low adherence towards physical distancing. Knowledge is one of the factors which determines the adherence towards physical distancing. Knowledge about COVID-19 should be known by everyone, including medical students. The purpose of this study was to determine the relationship between the knowledge level of COVID-19 and the adherence of physical distancing practice among final year medical students of the Universitas Pembangunan Nasional Veteran Jakarta Faculty of Medicine in 2020. This study used an observational analytic research design with a cross sectional approach. Simple random sampling was used for sampling method and data were analyzed by using chi square test. Primary data were taken from 120 respondents who filled out an online questionnaire via google form. Univariate analysis showed 67 respondents (55.8%) with good knowledge of COVID-19 and 70 respondents (58.3%) with good adherence to physical distancing. Bivariate analysis using the chi square test showed that there is no significant relationship between the knowledge level of COVID-19 and the adherence of physical distancing practice among final year medical students of the Universitas Pembangunan Nasional Veteran Jakarta Faculty of Medicine in 2020 (p = 0.203). These findings can be caused by other factors such as sociocultural. Particularly sociocultural factors in the sphere between friends, family or relatives, and the culture in the learning environment can affect adherence of physical distancing practice.